Anamórfica - Siqueira, Thais; Bezerra, Marina Deliperi; Paschoal, Gabrielly; Veiga, Beatriz Ximenez Alvez Martinez; Tinen, Milena Akemi (Universidade Federal de São Carlos, 2021)
Short film: A young woman contemplates her current circumstances and the choices she made to arrive at this point in her life, all while navigating the complexities of adulthood. On her quest for personal satisfaction, she gathers newfound inspiration by revisiting various stages of her journey.
Anamorphic
Keywords: Cinema; Audiovisual; Film; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::ROTEIRO E DIRECAO CINEMATOGRAFICOS